THE STRATEGY OF IMPLEMENTING A PARENTS' COMMUNICATION PATTERNS ON DEVIATING CHILDREN'S BEHAVIORAL - Suryani, Lilis (International Journal of Multidisciplinary Research and Literature, 2022)
The research approach used by the researcher is field research, with a descriptive qualitative approach that is observed from the point of view of applying parental communication patterns to the behaviour of children in Tangerang City, Banten. This study uses a sampling technique with special characteristics. Data collection is from observations, interviews and documentation with data analysis techniques, namely data presentation and concluding. The researchers found that a child needs communication between parents and children. The lack of communication between parents and children will affect children's behaviour, and One of the things that can support effective communication with children is communication. Poor communication between parents and children can worsen the relationship between parents and children. The success of contact with children shows passion between children and parents. Parents should try to explore the child's character. After examining the child's personality, the child thinks that their parents do not only see us but also the child will consider his parents as friends, so the child well received the message we sent.